Hardware-In-The-Loop Assessment for Continuous Set Model Predictive Control of a Modular Multilevel Matrix Converter - Diaz-Diaz, M; Uriarte-Gonzalez, M (Institute of Electrical and Electronics Engineers Inc., 2024)
This paper presents the validation of a Continuous Control Set Model Predictive Control (CCS-MPC) algorithm for a 27-cell Modular Multilevel Matrix Converter (M3C) operating between two three-phase power grids of different frequencies. The work focuses on implementing a Hardware-in-the-Loop (HIL) system specifically designed for this validation. The validation of the converter control strategy through HIL is performed using the dSPACE MicroLabBox and PLECS RT-Box platforms. The experimental tests encompass scenarios in both stationary and dynamic conditions. Notably, the algorithm s performance is assessed during instances of frequency variations within one of the power grids. The outcomes of these tests are notably encouraging, validating the effectiveness of the control strategy in maintaining the stable operation of the converter and adapting to variations in operating conditions. © 2024 IEEE.